(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Krishna’s® She Care Juice is a polyherbal preparation that is intended to promote women’s reproductive health, especially in the management of conditions such as Polycystic Ovary Syndrome (PCOS), irregular menstrual cycles, dysmenorrhea, and other gynecological disorders. This review summarizes the existing scientific and clinical literature regarding the major herbal constituents of the product i.e., Saraca asoca, Berberis aristata, Zingiber officinale, and Triphala emphasizing their unique roles in modifying hormonal equilibrium, anti-inflammatory actions, uterine health promotion, and enhancing metabolic indices. Clinical trials of S. asoca establish its effectiveness in curtailing menstrual bleeding and dysmenorrhea. B. aristata demonstrated insulin-sensitizing activity, useful in the management of PCOS, while Z. officinale has evidence based on randomized controlled trials for its analgesic and hormone-modulating action. Triphala, exhibiting antioxidant and adaptogenic activities, proved useful in the control of menstrual disorders, Premenstrual syndrome (PMS), and endometriosis. While encouraging evidence exists for each of these individual herbs, a major gap still exists in direct clinical evidence comparing the safety, tolerability, and efficacy of the combination formulation as it occurs in Krishna’s® She Care Juice. This serves to underscore the imperative need for pre-clinical mechanistic studies and rigorously designed clinical trials to establish its therapeutic merits, refine dosing regimens, and define safety profiles. The novel traditional application and corroborative findings on its components render Krishna’s® She Care Juice an interesting subject for future investigation, with the potential to become a standardized, evidence-based Ayurvedic treatment for women’s health.